2012
DOI: 10.1111/j.1742-6723.2012.01540.x
|View full text |Cite
|
Sign up to set email alerts
|

One hundred tasks an hour: An observational study of emergency department consultant activities

Abstract: Objective: To determine work activity patterns undertaken by ED consultants. Methods: A single observer time‐motion study of consultants rostered to clinical shifts: primarily administrative (Duty) or clinical (Resuscitation). Direct observation of 130 h was undertaken using purpose developed time‐stamping software. Primary outcome was task number and time spent in predetermined categories of activity. Comparisons occurred by role delineation, sex, weekday and time of day. Results: For each observed hour consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 18 publications
1
34
0
3
Order By: Relevance
“…Similarly, Kee et al reported that consultants undertook more than 100 tasks an hour 15. This is higher than the 34 tasks per hour as reported by France et al 26 or 80 tasks per working day as reported by Mache et al 21…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, Kee et al reported that consultants undertook more than 100 tasks an hour 15. This is higher than the 34 tasks per hour as reported by France et al 26 or 80 tasks per working day as reported by Mache et al 21…”
Section: Resultsmentioning
confidence: 88%
“…Sometimes it was reported as charting or dictation,17 24 26 paperwork22 27 or ‘data’19 but it basically referred to the recording of patient information on paper, or on the computer. Time spent on documentation ranged from around 10% in the Australian study by Kee et al 15 to as high as 28% according to Chisholm et al 16. In four studies, documentation occupied more than 20% of the senior doctors’ time 16 17 22 26…”
Section: Resultsmentioning
confidence: 99%
“…A Swedish study also identified that information exchange was the most common ED activity to be multitasked 56. Gender differences in communication loads for ED consultants suggest that females engage in higher activity 57. ED physicians have been shown to encounter up to 15 interruptions per hour, with senior doctors and nurses more frequently affected 58 59…”
Section: Resultsmentioning
confidence: 99%
“…Le modèle qui définit l'encombrement des urgences sanitaires suit alors l'évolution [entrée patient (urgent et non urgent) → soins urgents et non urgents → sortie] [26][27][28]. [29] KeeR and al a objectivé que chaque personnel des services des urgences réalise 101 tâches par heure ; 42% en communication, 35% en attitudes de soin clinique et 24% à l'usage de l'ordinateur et seulement 9% en attitudes non cliniques. L'activité médicale est potentiellement dangereuse : c'est ce qu'a mis en évidence le rapport « To err is human » en 2000 aux États-Unis [30].…”
Section: Concept D'urgence : Genese Et Evolution Dans Le Tempsunclassified